Waterproof heat-resistant adhesive and preparation method thereof
By combining modified epoxy resin and nano-oxidized carbon fibers and combined with the crosslinking effect of phenyl malic anhydride, the problems of insufficient waterproof and heat resistance of epoxy resin adhesives are solved, and efficient waterproof and heat resistance are achieved.
Patent Information
- Application Number
- CN202411493825.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
After curing, existing epoxy resin adhesives have problems such as brittle quality, poor toughness, poor waterproofing effect and poor heat resistance.
By making a homemade hydroxyl-terminated organic fluoro-silicon oil modified epoxy resin, nano-oxidized carbon fibers with vulcanized rubber powder attached to the surface as hybrid filler, and combining phenyl acrylic anhydride as a crosslinking agent, a tight three-dimensional crosslinking structure is formed.
The waterproof and heat resistance of the modified epoxy resin has been significantly improved, and the adhesive can still maintain good bonding strength under water treatment and high temperature conditions.
Smart Images

Figure BDA0005100761560000081 
Figure BDA0005100761560000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, in particular to a waterproof and heat-resistant adhesive and a preparation method thereof. Background Art
[0002] Epoxy resin adhesives have many excellent properties, such as high bonding strength, low shrinkage, wide bonding area, high mechanical strength, good processability, chemical resistance, simple preparation method, etc. They are currently playing an increasingly important role in many fields such as machinery, electronics, coatings, aerospace, and transportation.
[0003] Although epoxy resin adhesives are widely used, on the one hand, the main chain of epoxy resin contains many benzene rings and heterocycles, and the molecular chain has low flexibility, which makes the epoxy resin brittle and poor in toughness after curing, and the waterproof effect is not very ideal. On the other hand, epoxy resin itself has a three-dimensional structure, lacks sliding between molecular chains, has small bond energies of CC bonds and CH bonds, has high surface energy, and has some structural characteristics such as hydroxyl groups, which makes it brittle and easy to degrade at high temperatures. The adhesive made from it has the defect of poor heat resistance. Under high temperature conditions, it is easy to age and lose viscosity, which makes the adhesive made of epoxy resin as raw material have shortcomings in daily application. Summary of the invention
[0004] The object of the present invention is to provide a waterproof and heat-resistant adhesive and a preparation method thereof to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a waterproof and heat-resistant adhesive, wherein the homemade hydroxyl-terminated organic fluorosilicone oil-modified epoxy resin is cross-linked after adding a hybrid filler, and then the adhesive is prepared using the epoxy resin as a raw material.
[0006] Furthermore, the hybrid filler is nano-oxidized carbon fiber with vulcanized rubber powder attached to the surface.
[0007] Furthermore, the cross-linking agent is phenyl maleic anhydride.
[0008] Furthermore, a method for preparing a waterproof and heat-resistant adhesive comprises the following preparation steps:
[0009] (1) Add 100 parts of tetramethyl tri-3-trifluoropropyl cyclotetrasiloxane, 1 to 3 parts of dodecylamine, 4 to 6 parts of deionized water, and 1 to 2 parts of ether to a mechanical reactor, stir at 200 rpm for 30 minutes, raise the temperature of the reactor to 40 to 100°C, maintain this temperature for 2 to 6 hours, then add 100 g of hydrochloric acid, continue stirring for 2 hours to make the reaction system neutral, add 2 parts of diatomaceous earth, stir for 30 minutes, filter press, transfer the filtrate to a distillation kettle, and heat. The temperature was raised to 130°C, the system pressure was maintained at 500Pa, and after evacuation for 8 hours, the vacuum degree was 200Pa, and hydroxyl-terminated organic fluorosilicone oil was obtained; 20 parts by mass of WSR-6101 epoxy resin, 0.3-0.6 parts of acidic catalyst and 40 parts of toluene were added to the reaction kettle, nitrogen was passed through, the temperature was raised to 80°C, 10-20 parts of hydroxyl-terminated organic fluorosilicone oil were added dropwise, and the dripping was completed within 5 hours. After the dripping was completed, the reaction was continued at 80°C for 10 hours; the solvent was removed by distillation under reduced pressure, and the catalyst was removed by silica gel to obtain a modified epoxy resin;
[0010] (2) At room temperature, a mixed aqueous solution of potassium permanganate and sulfuric acid is prepared, and then a carbon fiber with a diameter of 200 nm is placed in the mixed solution of potassium permanganate and sulfuric acid, with a solid-liquid mass ratio of 1 to 1.6:10, and placed in a supercritical device, and reacted for 15 to 25 minutes in a system at a temperature of 300 to 350°C and a pressure of 0.085 MPa, and then the carbon fiber is taken out and placed in a beaker filled with hydrochloric acid, with a solid-liquid ratio of 1:5, and after sealing, it is placed in a water bath at 60 to 80°C and soaked for 2 to 4 hours; it is placed in a Soxhlet extractor again, and the carbon fiber is washed with ethanol at 80°C for 2 hours, with a solid-liquid ratio of 1:5, and then the carbon fiber is taken out and placed in a 50°C oven for drying for 2 to 4 hours to obtain oxidized carbon fiber; dimethyl methyl vinyl with a solid content of 40% is added The silicone rubber is placed in a plastic container, trimethylolpropane triacrylate is added while stirring at a speed of 250 rpm, and then stirring is continued for one hour, and then irradiated with a cobalt source with a dosage of 20 Mrad; after the irradiation, spray drying is performed with a spray dryer, the inlet temperature of the spray dryer is 120-160°C, and the outlet temperature is 40-80°C, and the dried vulcanized rubber powder is collected in a cyclone separator; the vulcanized rubber powder, oxidized carbon fiber, and deionized water are mixed in a mass ratio of 1:0.5-2:10, stirred at a speed of 60 rpm for 10 minutes, and then ultrasonically treated with a power of 40 kHz for 30 minutes, and centrifuged at a speed of 12000 rpm for 20 minutes after the treatment, and the solid is taken and then dried at 50°C for 2 hours to obtain a hybrid filler;
[0011] (3) Phenyl maleic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol were added to a reactor at a mass ratio of 50 to 80:1, and stirred at a high speed of 3000 rpm for 1 to 2 hours at 25°C to uniformly disperse the two, thereby obtaining a mixture A; modified epoxy resin and hybrid filler were added to a reactor at a mass ratio of 40 to 50:1, and stirred at a speed of 400 rpm for 3 hours at 50°C to uniformly disperse the two, thereby obtaining a mixture B; mixture A and mixture B were added to a reactor, and stirred at a speed of 3000 to 5000 rpm and 20°C for 3 to 5 minutes to obtain an epoxy resin adhesive.
[0012] Furthermore, the acidic catalyst in step (1) is potassium carbonate.
[0013] Furthermore, the concentration of hydrochloric acid in step (1) is 20%.
[0014] Furthermore, in the mixed aqueous solution of potassium permanganate and sulfuric acid in step (2), the concentration of potassium permanganate is 1-2%, and the concentration of sulfuric acid is 36-56%.
[0015] Furthermore, the concentration of hydrochloric acid in step (2) is 35%.
[0016] Furthermore, the mass ratio of dimethyl methyl vinyl silicone rubber to trimethylolpropane triacrylate in step (2) is 10:0.15-0.3.
[0017] Furthermore, in step (3), the mass ratio of mixture A to mixture B is 2:3-4.
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0019] The invention prepares a self-made hydroxyl-terminated organic fluorosilicone oil-modified epoxy resin, adds a hybrid filler and cross-links it with phenyl maleic anhydride, and then uses the epoxy resin as a raw material to prepare an adhesive to achieve waterproof and heat-resistant effects.
[0020] Firstly, hydroxyl-terminated organic fluorosilicone oil is prepared with tetramethyl tri-3-trifluoropropyl cyclotetrasiloxane as raw material and water as end-capping agent, and then reacted with epoxy resin to form modified epoxy resin with organic fluorosilicone as side chain. There are 4 groups of fluorine atoms on one side chain, which are spread out like an umbrella and closely arranged around its main chain, thereby achieving the effect of reducing surface tension, and cooperating with organic silicon to further reduce the surface energy of the modified epoxy resin, thereby improving the waterproof effect of the modified epoxy resin. Because of the introduction of high bond energy fluorine atom bundles, the thermal stability of the epoxy resin is also improved; the surface of the nano-scale carbon fiber is oxidized to make its surface rich in hydroxyl; the hydroxyl groups on the oxidized nano-carbon fiber react and combine with the thiocyanate in the vulcanized rubber powder to form oxidized carbon fiber with vulcanized rubber powder attached to the surface as a hybrid filler; and the surface of the oxidized carbon fiber has carboxyl groups and some acidic groups in addition to hydroxyl groups, and these remaining active groups are then combined with the epoxy resin for cross-linking, which optimizes the dispersibility and compatibility of the hybrid filler, and the addition of vulcanized rubber and carbon fiber also greatly improves the heat resistance of the epoxy resin;
[0021] Secondly, phenyl maleic anhydride is used as a cross-linking agent to form ion pairs, which continuously react with epoxy groups to form a three-dimensional cross-linked structure. This tight three-dimensional cross-linked structure can make it more difficult for water molecules to enter the epoxy resin. At the same time, phenyl groups are introduced into the structure to further improve the heat resistance and waterproof effects of the epoxy resin, so that the adhesive prepared with this epoxy resin as raw material has excellent waterproof and heat resistance. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of a waterproof and heat-resistant adhesive prepared in the following examples as follows:
[0024] Waterproofness: The examples and comparative examples were coated on aluminum alloy plates, and the amount of glue applied was controlled at 100 g / m 3 , then cure the coated board at 80℃ for 2h, and measure the bonding strength; then soak it in water for 24h at 20℃, and measure its bonding strength after taking it out; calculate its bonding strength retention rate after water treatment;
[0025] Heat resistance: The examples and comparative examples were coated on aluminum alloy plates, and the coating amount was controlled at 100 g / m 3, then the coated board was cured at 80℃ for 2h, and the bonding strength was measured; then it was placed in a blast drying oven for heat treatment at 300℃ for 30min, and the bonding strength was tested again after cooling; the bonding strength retention rate after heat treatment was calculated;
[0026] Example 1
[0027] (1) Add 100 parts of tetramethyl tri-3-trifluoropropyl cyclotetrasiloxane, 1 part of dodecylamine, 4 parts of deionized water, and 1 part of ether to a mechanical reactor, stir at 200 rpm for 30 minutes, raise the temperature of the reactor to 40°C, maintain this temperature for 2 hours, then add 100 g of 20% hydrochloric acid, continue stirring for 2 hours to make the reaction system neutral, add 2 parts of diatomaceous earth, stir for 30 minutes, filter, and transfer the filtrate to a distillation kettle. , the temperature was raised to 130°C, the system pressure was maintained at 500Pa, and after evacuation for 8 hours, the vacuum degree was 200Pa, and hydroxyl-terminated organic fluorosilicone oil was obtained; 20 parts by mass of WSR-6101 epoxy resin, 0.3 parts of potassium carbonate and 40 parts of toluene were added to the reaction kettle, nitrogen was passed through, the temperature was raised to 80°C, 10 parts of hydroxyl-terminated organic fluorosilicone oil were added dropwise, and the dripping was completed within 5 hours. After the dripping was completed, the reaction was continued at 80°C for 10 hours; the solvent was removed by distillation under reduced pressure, and the catalyst was removed by silica gel to obtain a modified epoxy resin;
[0028] (2) At room temperature, a mixed aqueous solution of potassium permanganate and sulfuric acid is prepared, wherein the concentration of potassium permanganate is 1% and the concentration of sulfuric acid is 36%. Then, a carbon fiber with a diameter of 200 nm is placed in the mixed solution of potassium permanganate and sulfuric acid, with a solid-liquid mass ratio of 1:10, and placed in a supercritical device, and reacted for 15 minutes in a system at a temperature of 300°C and a pressure of 0.085MPa. Then, the carbon fiber is taken out and placed in a beaker filled with 35% hydrochloric acid, with a solid-liquid ratio of 1:5. After sealing, it is placed in a 60°C water bath and soaked for 2 hours; it is placed in a Soxhlet extractor again, and the carbon fiber is washed with ethanol at 80°C for 2 hours, with a solid-liquid ratio of 1:5. Then, the carbon fiber is taken out and placed in a 50°C oven for drying for 2 hours to obtain oxidized carbon fiber; dimethyl methyl vinyl silicone rubber with a solid content of 40% is placed in a plastic In a container, trimethylolpropane triacrylate is added while stirring at a speed of 250 rpm, so that the mass ratio of dimethyl methyl vinyl silicone rubber to trimethylolpropane triacrylate is 10:0.15, and then stirring is continued for one hour, and then irradiated with a cobalt source with a dosage of 20 Mrad; after the irradiation, spray drying is performed with a spray dryer, the inlet temperature of the spray dryer is 120°C, and the outlet temperature is 40°C, and the dried vulcanized rubber powder is collected in a cyclone separator; the vulcanized rubber powder, oxidized carbon fiber, and deionized water are mixed in a mass ratio of 1:0.5:10, stirred at a speed of 60 rpm for 10 minutes, and then ultrasonically treated with a power of 40 kHz for 30 minutes. After the treatment, centrifugation is performed at a speed of 12000 rpm for 20 minutes, and the solid is taken and then dried at 50°C for 2 hours to obtain a hybrid filler;
[0029] (3) Phenyl maleic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol were added to a reactor in a mass ratio of 50:1, and stirred at a high speed of 3000 rpm for 1 hour at 25°C to uniformly disperse the two, thereby obtaining a mixture A; modified epoxy resin and hybrid filler were added to a reactor in a mass ratio of 40:1, and stirred at a speed of 400 rpm for 3 hours at 50°C to uniformly disperse the two, thereby obtaining a mixture B; mixture A and mixture B were added to a reactor in a mass ratio of 2:3, and stirred at a speed of 3000 rpm and 20°C for 3 minutes to obtain an epoxy resin adhesive.
[0030] Example 2
[0031] (1) Add 100 parts of tetramethyl tri-3-trifluoropropyl cyclotetrasiloxane, 2 parts of dodecylamine, 5 parts of deionized water, and 1.5 parts of ether to a mechanical reactor, stir at 200 rpm for 30 minutes, raise the temperature of the reactor to 70°C, maintain this temperature for 4 hours, then add 100 g of 20% hydrochloric acid, continue stirring for 2 hours to make the reaction system neutral, add 2 parts of diatomaceous earth, stir for 30 minutes, filter, and transfer the filtrate to a distillation kettle. , the temperature was raised to 130°C, the system pressure was maintained at 500Pa, and after evacuation for 8 hours, the vacuum degree was 200Pa, and hydroxyl-terminated organic fluorosilicone oil was obtained; 20 parts by mass of WSR-6101 epoxy resin, 0.45 parts of potassium carbonate and 40 parts of toluene were added to the reaction kettle, nitrogen was passed through, the temperature was raised to 80°C, 15 parts of hydroxyl-terminated organic fluorosilicone oil were added dropwise, and the dripping was completed within 5 hours. After the dripping was completed, the reaction was continued at 80°C for 10 hours; the solvent was removed by distillation under reduced pressure, and the catalyst was removed by silica gel to obtain a modified epoxy resin;
[0032] (2) At room temperature, a mixed aqueous solution of potassium permanganate and sulfuric acid is prepared, wherein the concentration of potassium permanganate is 1.5% and the concentration of sulfuric acid is 46%. Then, a carbon fiber with a diameter of 200 nm is placed in the mixed solution of potassium permanganate and sulfuric acid, with a solid-liquid mass ratio of 1.3:10, and placed in a supercritical device, and reacted for 20 minutes in a system at a temperature of 325°C and a pressure of 0.085MPa. Then, the carbon fiber is taken out and placed in a beaker filled with 35% hydrochloric acid with a solid-liquid ratio of 1:5. After sealing, it is placed in a 70°C water bath and soaked for 3 hours; it is placed in a Soxhlet extractor again, and the carbon fiber is washed with ethanol at 80°C for 2 hours with a solid-liquid ratio of 1:5. Then, the carbon fiber is taken out and placed in a 50°C oven for drying for 3 hours to obtain oxidized carbon fiber; dimethyl methyl vinyl silicone rubber with a solid content of 40% is placed in a plastic container In a device, trimethylolpropane triacrylate is added while stirring at a speed of 250rpm, so that the mass ratio of dimethyl methyl vinyl silicone rubber to trimethylolpropane triacrylate is 10:0.225, and then stirring is continued for one hour, and then irradiated with a cobalt source with a dosage of 20Mrad; after the irradiation, spray drying is performed in a spray dryer, the inlet temperature of the spray dryer is 140°C, and the outlet temperature is 40-80°C, and the dried vulcanized rubber powder is collected in a cyclone separator; the vulcanized rubber powder, oxidized carbon fiber, and deionized water are mixed in a mass ratio of 1:1.25:10, stirred at a speed of 60rpm for 10min, and then ultrasonically treated at a power of 40kHz for 30min, and centrifuged at a speed of 12000rpm for 20min after the treatment, and the solid is taken and then dried at 50°C for 2h to obtain a hybrid filler;
[0033] (3) Phenyl maleic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol were added to the reactor in a mass ratio of 65:1, and stirred at a high speed of 3000 rpm for 1.5 hours at 25°C to uniformly disperse the two to obtain a mixture A; modified epoxy resin and hybrid filler were added to the reactor in a mass ratio of 45:1, and stirred at a speed of 400 rpm for 3 hours at 50°C to uniformly disperse the two to obtain a mixture B; mixture A and mixture B were added to the reactor in a mass ratio of 2:3.5, and stirred at a speed of 4000 rpm and 20°C for 4 minutes to obtain an epoxy resin adhesive.
[0034] Example 3
[0035] (1) Add 100 parts of tetramethyl tri-3-trifluoropropyl cyclotetrasiloxane, 3 parts of dodecylamine, 6 parts of deionized water, and 2 parts of ether to a mechanical reactor, stir at 200 rpm for 30 minutes, raise the temperature of the reactor to 100°C, maintain this temperature for 6 hours, then add 100 g of 20% hydrochloric acid, continue stirring for 2 hours to make the reaction system neutral, add 2 parts of diatomaceous earth, stir for 30 minutes, filter, and transfer the filtrate to a distillation kettle. , the temperature was raised to 130°C, the system pressure was maintained at 500Pa, and after evacuation for 8 hours, the vacuum degree was 200Pa, and hydroxyl-terminated organic fluorosilicone oil was obtained; 20 parts by mass of WSR-6101 epoxy resin, 0.6 parts of potassium carbonate and 40 parts of toluene were added to the reaction kettle, nitrogen was passed through, the temperature was raised to 80°C, 20 parts of hydroxyl-terminated organic fluorosilicone oil were added dropwise, and the dripping was completed within 5 hours. After the dripping was completed, the reaction was continued at 80°C for 10 hours; the solvent was removed by distillation under reduced pressure, and the catalyst was removed by silica gel to obtain a modified epoxy resin;
[0036] (2) At room temperature, a mixed aqueous solution of potassium permanganate and sulfuric acid is prepared, wherein the concentration of potassium permanganate is 2% and the concentration of sulfuric acid is 56%. Then, a carbon fiber with a diameter of 200 nm is placed in the mixed solution of potassium permanganate and sulfuric acid, with a solid-liquid mass ratio of 1.6:10, and placed in a supercritical device, and reacted for 25 minutes in a system at a temperature of 350°C and a pressure of 0.085MPa. Then, the carbon fiber is taken out and placed in a beaker filled with 35% hydrochloric acid with a solid-liquid ratio of 1:5. After sealing, it is placed in a water bath at 80°C and soaked for 4 hours; it is placed in a Soxhlet extractor again, and the carbon fiber is washed with ethanol at 80°C for 2 hours with a solid-liquid ratio of 1:5. Then, the carbon fiber is taken out and placed in a 50°C oven for drying for 4 hours to obtain oxidized carbon fiber; dimethyl methyl vinyl silicone rubber with a solid content of 40% is placed in a In a plastic container, trimethylolpropane triacrylate is added while stirring at a speed of 250rpm, so that the mass ratio of dimethyl methyl vinyl silicone rubber to trimethylolpropane triacrylate is 10:0.3, and then stirring is continued for one hour, and then irradiated with a cobalt source with a dosage of 20Mrad; after the irradiation, spray drying is performed in a spray dryer, the inlet temperature of the spray dryer is 160°C, and the outlet temperature is 80°C, and the dried vulcanized rubber powder is collected in a cyclone separator; the vulcanized rubber powder, oxidized carbon fiber, and deionized water are mixed in a mass ratio of 1:2:10, stirred at a speed of 60rpm for 10min, and then ultrasonically treated at a power of 40kHz for 30min, and centrifuged at a speed of 12000rpm for 20min after the treatment, and the solid is taken and then dried at 50°C for 2h to obtain a hybrid filler;
[0037] (3) Phenyl maleic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol were added to a reactor at a mass ratio of 80:1, and stirred at a high speed of 3000 rpm for 2 hours at 25°C to uniformly disperse the two, thereby obtaining a mixture A; modified epoxy resin and hybrid filler were added to a reactor at a mass ratio of 50:1, and stirred at a speed of 400 rpm for 3 hours at 50°C to uniformly disperse the two, thereby obtaining a mixture B; mixture A and mixture B were added to a reactor at a mass ratio of 2:4, and stirred at a speed of 5000 rpm and 20°C for 5 minutes to obtain an epoxy resin adhesive.
[0038] Comparative Example 1
[0039] The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: add 20 parts by mass of WSR-6101 epoxy resin, 0.45 parts of potassium carbonate and 40 parts of toluene to the reaction kettle, pass nitrogen, heat to 80°C, add 15 parts of tetramethyl tri-3-trifluoropropyl cyclotetrasiloxane dropwise, and add it dropwise for 5 hours. After the addition is completed, continue the reaction at 80°C for 10 hours; remove the solvent by distillation under reduced pressure, remove the catalyst by silica gel, and obtain a modified epoxy resin; the remaining steps are the same as those in Example 2.
[0040] Comparative Example 2
[0041] The difference between Comparative Example 2 and Example 2 is that there is no step (1), and step (3) is changed to: phenyl maleic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol are added to a reactor in a mass ratio of 65:1, and stirred at a high speed of 3000 rpm for 1.5 hours at 25°C to uniformly disperse the two to obtain a mixture A; WSR-6101 epoxy resin and hybrid filler are added to a reactor in a mass ratio of 45:1, and stirred at a speed of 400 rpm for 3 hours at 50°C to uniformly disperse the two to obtain a mixture B; Mixture A and mixture B are added to a reactor in a mass ratio of 2:3.5, and stirred at a speed of 4000 rpm and 20°C for 4 minutes to obtain an epoxy resin adhesive; the remaining steps are the same as in Example 2.
[0042] Comparative Example 3
[0043] The difference between Comparative Example 3 and Example 2 lies in the difference in steps (2) and (3). Steps (2) and (3) are changed to: (2) placing dimethyl methyl vinyl silicone rubber with a solid content of 40% in a plastic container, adding trimethylolpropane triacrylate at a stirring speed of 250 rpm so that the mass ratio of dimethyl methyl vinyl silicone rubber to trimethylolpropane triacrylate is 10:0.225, and then continuing to stir for one hour, and then irradiating with a cobalt source at a dosage of 20 Mrad; after the irradiation, spray drying is performed in a spray dryer, the inlet temperature of the spray dryer is 140°C, and the outlet temperature is 40-80°C, and the dried vulcanized rubber powder is collected in a cyclone separator;
[0044] (3) Phenyl maleic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol were added to a reactor in a mass ratio of 65:1, and stirred at a high speed of 3000 rpm for 1.5 h at 25°C to uniformly disperse the two to obtain a mixture A; modified epoxy resin and vulcanized rubber powder were added to a reactor in a mass ratio of 45:1, and stirred at a speed of 400 rpm for 3 h at 50°C to uniformly disperse the two to obtain a mixture B; mixture A and mixture B were added to a reactor in a mass ratio of 2:3.5, and stirred at a speed of 4000 rpm and 20°C for 4 min to obtain an epoxy resin adhesive; the remaining steps were the same as in Example 2.
[0045] Comparative Example 4
[0046] The difference between Comparative Example 4 and Example 2 is that step (2) is different. Step (2) is changed to: at room temperature, a mixed aqueous solution of potassium permanganate and sulfuric acid is prepared, wherein the concentration of potassium permanganate is 1.5% and the concentration of sulfuric acid is 46%, and then a carbon fiber with a diameter of 200 nm is placed in the mixed solution of potassium permanganate and sulfuric acid, with a solid-liquid mass ratio of 1.3:10, and placed in a supercritical device, and reacted for 20 minutes in a system at a temperature of 325°C and a pressure of 0.085MPa, and then the carbon fiber is taken out and placed in a beaker filled with 35% hydrochloric acid, with a solid-liquid ratio of 1:5, and after sealing, placed in a 70°C water bath and soaked it for 3 hours; put it into the Soxhlet extractor again, and wash the carbon fiber with ethanol at 80°C for 2 hours, with a solid-liquid ratio of 1:5, then take out the carbon fiber, and dry it in a 50°C oven for 3 hours to obtain oxidized carbon fiber; dimethyl methyl vinyl silicone rubber powder, oxidized carbon fiber, and deionized water are mixed in a mass ratio of 1:1.25:10, stirred at 60rpm for 10min, and then ultrasonically treated at a power of 40kHz for 30min. After the treatment, centrifuge at 12000rpm for 20min, take the solid and then dry it at 50°C for 2h to obtain a hybrid filler; the remaining steps are the same as Example 2.
[0047] Comparative Example 5
[0048] The difference between Comparative Example 5 and Example 2 is that step (3) is different. Step (3) is changed to: maleic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol are added to the reactor in a mass ratio of 65:1, and stirred at a high speed of 3000 rpm for 1.5 hours at 25°C to uniformly disperse the two to obtain a mixture A; the modified epoxy resin and the hybrid filler are added to the reactor in a mass ratio of 45:1, and stirred at a speed of 400 rpm for 3 hours at 50°C to uniformly disperse the two to obtain a mixture B; the mixture A and the mixture B are added to the reactor in a mass ratio of 2:3.5, and stirred at a speed of 4000 rpm and 20°C for 4 minutes to obtain an epoxy resin adhesive; the remaining steps are the same as in Example 2.
[0049] Effect example
[0050] Table 1 below shows a waterproof and heat-resistant adhesive using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0051] Performance analysis results.
[0052] Table 1
[0053]
[0054]
[0055] From the experimental data comparison of the bonding strength retention rate after water treatment of the embodiment and the comparative example, it can be found that the present invention uses tetramethyl tri-3-trifluoropropyl cyclotetrasiloxane as raw material and water as end-capping agent to prepare hydroxyl-terminated organic fluorosilicone oil, and reacts with epoxy resin to form a modified epoxy resin with organic fluorosilicone as a branch chain, and there are 4 groups of fluorine atoms on a branch chain, which are opened like an umbrella, and are closely arranged around its main chain to present, so as to achieve the effect of reducing surface tension, and further reduce the surface energy of the modified epoxy resin in collaboration with organosilicon, so as to improve the waterproof effect of the modified epoxy resin. The present invention uses phenyl maleic anhydride as a cross-linking agent to form an ion pair, and continuously reacts with epoxy groups to form a three-dimensional cross-linked structure, and this tight three-dimensional cross-linked structure can make water molecules more difficult to enter the epoxy resin. From the experimental data comparison of the bonding strength retention rate after heat treatment of the embodiment and the comparative example, it can be found that the present invention is because of the introduction of high bond energy fluorine atom beams, and the thermal stability of epoxy resin is also improved. The present invention performs surface oxidation treatment on nano-scale carbon fiber to enrich its surface with hydroxyl groups; the hydroxyl groups on the oxidized nano-carbon fiber react and combine with the thiocyanate in the vulcanized rubber powder to form an oxidized carbon fiber with the vulcanized rubber powder attached to the surface as a hybrid filler; and the surface of the oxidized carbon fiber has carboxyl groups and some acidic groups in addition to hydroxyl groups, and these remaining active groups are cross-linked with epoxy resin, which optimizes the dispersibility and compatibility of the hybrid filler, and the addition of vulcanized rubber and carbon fiber also greatly improves the heat resistance of the epoxy resin. At the same time, phenyl groups are introduced during cross-linking to further improve the heat resistance of the epoxy resin, so that the adhesive prepared with the epoxy resin as a raw material has excellent waterproof and heat resistance.
[0056] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A waterproof and heat-resistant adhesive, characterized in that: The self-made hydroxyl-terminated organic fluorosilicone oil-modified epoxy resin is cross-linked after adding a hybrid filler, and then the adhesive is prepared using the epoxy resin as a raw material.
2. A waterproof and heat-resistant adhesive according to claim 1, characterized in that: The hybrid filler is nano-oxidized carbon fiber with vulcanized rubber powder attached to the surface.
3. The waterproof and heat-resistant adhesive according to claim 1, characterized in that: The cross-linking agent is phenyl maleic anhydride.
4. A method for preparing a waterproof and heat-resistant adhesive, characterized in that: The method comprises the following preparation steps: (1) Add 100 parts of tetramethyl tri-3-trifluoropropyl cyclotetrasiloxane, 1 to 3 parts of dodecylamine, 4 to 6 parts of deionized water, and 1 to 2 parts of ether to a mechanical reactor, stir at 200 rpm for 30 minutes, raise the temperature of the reactor to 40 to 100°C, maintain this temperature for 2 to 6 hours, then add 100 g of hydrochloric acid, continue stirring for 2 hours to make the reaction system neutral, add 2 parts of diatomaceous earth, stir for 30 minutes, filter press, transfer the filtrate to a distillation kettle, and heat. The temperature was raised to 130°C, the system pressure was maintained at 500Pa, and after evacuation for 8 hours, the vacuum degree was 200Pa, and hydroxyl-terminated organic fluorosilicone oil was obtained; 20 parts by mass of WSR-6101 epoxy resin, 0.3-0.6 parts of acidic catalyst and 40 parts of toluene were added to the reaction kettle, nitrogen was passed through, the temperature was raised to 80°C, 10-20 parts of hydroxyl-terminated organic fluorosilicone oil were added dropwise, and the dripping was completed within 5 hours. After the dripping was completed, the reaction was continued at 80°C for 10 hours; the solvent was removed by distillation under reduced pressure, and the catalyst was removed by silica gel to obtain a modified epoxy resin; (2) At room temperature, a mixed aqueous solution of potassium permanganate and sulfuric acid is prepared, and then a carbon fiber with a diameter of 200 nm is placed in the mixed solution of potassium permanganate and sulfuric acid, with a solid-liquid mass ratio of 1 to 1.6:10, and placed in a supercritical device, and reacted for 15 to 25 minutes in a system at a temperature of 300 to 350°C and a pressure of 0.085 MPa, and then the carbon fiber is taken out and placed in a beaker filled with hydrochloric acid, with a solid-liquid ratio of 1:5, and after sealing, it is placed in a water bath at 60 to 80°C and soaked for 2 to 4 hours; it is placed in a Soxhlet extractor again, and the carbon fiber is washed with ethanol at 80°C for 2 hours, with a solid-liquid ratio of 1:5, and then the carbon fiber is taken out and placed in a 50°C oven for drying for 2 to 4 hours to obtain oxidized carbon fiber; dimethyl methyl vinyl with a solid content of 40% is added The silicone rubber is placed in a plastic container, trimethylolpropane triacrylate is added while stirring at a speed of 250 rpm, and then stirring is continued for one hour, and then irradiated with a cobalt source with a dosage of 20 Mrad; after the irradiation, spray drying is performed with a spray dryer, the inlet temperature of the spray dryer is 120-160°C, and the outlet temperature is 40-80°C, and the dried vulcanized rubber powder is collected in a cyclone separator; the vulcanized rubber powder, oxidized carbon fiber, and deionized water are mixed in a mass ratio of 1:0.5-2:10, stirred at a speed of 60 rpm for 10 minutes, and then ultrasonically treated with a power of 40 kHz for 30 minutes, and centrifuged at a speed of 12000 rpm for 20 minutes after the treatment, and the solid is taken and then dried at 50°C for 2 hours to obtain a hybrid filler; (3) Phenyl maleic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol were added to a reactor at a mass ratio of 50 to 80:1, and stirred at a high speed of 3000 rpm for 1 to 2 hours at 25°C to uniformly disperse the two, thereby obtaining a mixture A; modified epoxy resin and hybrid filler were added to a reactor at a mass ratio of 40 to 50:1, and stirred at a speed of 400 rpm for 3 hours at 50°C to uniformly disperse the two, thereby obtaining a mixture B; mixture A and mixture B were added to a reactor, and stirred at a speed of 3000 to 5000 rpm and 20°C for 3 to 5 minutes to obtain an epoxy resin adhesive.
5. The method for preparing a waterproof and heat-resistant adhesive according to claim 4, characterized in that: The acidic catalyst in step (1) is potassium carbonate.
6. The method for preparing a waterproof and heat-resistant adhesive according to claim 4, characterized in that: The concentration of hydrochloric acid in step (1) is 20%.
7. The method for preparing a waterproof and heat-resistant adhesive according to claim 4, characterized in that: In the mixed aqueous solution of potassium permanganate and sulfuric acid in step (2), the concentration of potassium permanganate is 1-2%, and the concentration of sulfuric acid is 36-56%.
8. The method for preparing a waterproof and heat-resistant adhesive according to claim 4, characterized in that: The concentration of hydrochloric acid in step (2) is 35%.
9. The method for preparing a waterproof and heat-resistant adhesive according to claim 4, characterized in that: The mass ratio of dimethyl methyl vinyl silicone rubber to trimethylolpropane triacrylate in the step (2) is 10:0.15-0.
3.
10. The method for preparing a waterproof and heat-resistant adhesive according to claim 4, characterized in that: In the step (3), the mass ratio of mixture A to mixture B is 2:3-4.
Citation Information
Cited By
Abrasion-resistant industrial coating and manufacturing method thereof
CN121227162A
An abrasion-resistant industrial coating and method of making the same
CN121227162B
Aerogel for high-strength adhesive as well as preparation method and application of aerogel
CN121554817A
A high-strength adhesive aerogel, its preparation method and application
CN121554817B